Synchronous state of unbalanced rotors in a three-dimensional space and far-resonance system. (February 2020) - Fang, Pan; Peng, Huan; Changcheng, Du; Zou, Min; Hou, Duyu; Du, Mingjun; Chai, Guodong
The unreasonable dynamic characteristics results in decrease of screening efficiency of the vibrating screen. However, the synchronous behavior of motors is key factor to determine dynamic characteristics of the screens. In this paper, two unbalanced rotors actuated with motors in a three-dimensional space are proposed. To understand the synchronous mechanism, the dynamic equation of the system is firstly confirmed based on Lagrangian formulation; meanwhile, synchronization condition of the system is calculated with average and small parameter method; then, synchronization stability of the system is explored by Lyapunov method; finally, some numerical simulations are given to validate the theoretical computations. It is found that, to implement the stable synchronous rotation between the rotors, the values of the parameter in this system must be satisfied by synchronous condition and synchronous stability; the synchronous state is determined by the rotation direction, the damping ratio, the frequency ratio, and the motor position; the system is a planar motion when the identical mass rotors oppositely actuated, but the system is a spatial motion in the other cases.